Kajian Struktural Sastra Pada Cerpen Dua Orang Sahabat Karya A.A Navis - Ghina Ayu Salsabila; Rizka Maulidania; Aveny Septi Astriani (BADAN PENERBIT STIEPARI PRESS, 2023)
The aim of this study is to analyze the structural aspects contained in the short story